Structure-activity relationship studies of novel benzophenones leading to the discovery of a potent, next generation HIV nonnucleoside reverse transcriptase inhibitor. - Romines, K; Freeman, G; Schaller, LT; Cowan, JR; Gonzales, S; Tidwell, J; Andrews, C; Stammers, D; Hazen, R; Ferris, R; Short, SA; Chan, J; et al. (2006)
Despite the progress of the past two decades, there is still considerable need for safe, efficacious drugs that target human immunodeficiency virus (HIV). This is particularly true for the growing number of patients infected with virus resistant to currently approved HIV drugs. Our high throughput screening effort identified a benzophenone template as a potential nonnucleoside reverse transcriptase inhibitor (NNRTI). This manuscript describes our extensive exploration of the benzophenone structure-activity relationships, which culminated in the identification of several compounds with very potent inhibition of both wild type and clinically relevant NNRTI-resistant mutant strains of HIV. These potent inhibitors include 70h (GW678248), which has in vitro antiviral assay IC(50) values of 0.5 nM against wild-type HIV, 1 nM against the K103N mutant associated with clinical resistance to efavirenz, and 0.7 nM against the Y181C mutant associated with clinical resistance to nevirapine. Compound 70h has also demonstrated relatively low clearance in intravenous pharmacokinetic studies in three species, and it is the active component of a drug candidate which has progressed to phase 2 clinical studies.